Colostrum quality of ewe fed flushing diet containing EPA and DHA associated with lamb performance - Nurlatifah, A.; Khotijah, L.; Arifiantini, R. I.; Maidin, M. S.; Astuti, D. A. (Institut Pertanian Bogor, 2022)
This study evaluated the effect of a flushing diet containing docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) from lemuru fish oil in ewe ration on colostrum quality and lamb performance. Twenty Garut ewes were divided into four treatments of flushing concentrate: control concentrate (P1), flushing concentrate containing 6% palm oil (P2), flushing concentrate containing 3% lemuru oil and 3% palm oil (P3), flushing concentrate containing 6% lemuru oil (P4). The animal consumed Napier grass and concentrate with a diet ratio of 30%:70% based on dry matter. The experimental ewes were fed flushing rations two weeks before and two weeks after mating continued with 2 weeks before and two weeks after lambing. The ewes and their lambs were put together until weaning time with around two months. The parameters observed in ewes were nutrient consumption and their colostrum qualities. Meanwhile, the lamb parameters measured were nutrient consumption, lamb blood metabolites at birth, and lamb performance. The experimental design used a randomized blocked design (RBD). Analysis of variance (ANOVA) followed by Duncan test was used to analyze data. The results showed that treatment did not significantly affect dry matter consumption in ewe and lamb, ewe’s colostrum quality, and lamb’s blood metabolites. However, the treatment significantly improved (p<0.05) average daily gain and weaning weights of lambs. In conclusion, the flushing ration did not affect the quality of colostrum produced. Feeding of experimental ewes 2 weeks before and 2 weeks after mating continued with 2 weeks before and 2 weeks after parturition with flushing rations of 6% lemuru oil containing EPA and DHA can produce twin lambs with good growth performances such as daily gain and weaning weight similar to the control, which has single litter size.